2019
DOI: 10.3389/fcell.2019.00134
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus, Alzheimer’s Disease and a Possible Role for Rab GTPases

Abstract: Herpes simplex virus (HSV) is a common pathogen, infecting 85% of adults in the United States. After reaching the nucleus of the long-lived neuron, HSV may enter latency to persist throughout the life span. Re-activation of latent herpesviruses is associated with progressive cognitive impairment and Alzheimer’s disease (AD). As an enveloped DNA virus, HSV exploits cellular membrane systems for its life cycle, and thereby comes in contact with the Rab family of GTPases, master regulators of intracellular membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 110 publications
(156 reference statements)
0
18
0
Order By: Relevance
“…Hence not only would the APP-containing vesicles lose transport capability, but other organelles would have to compete with the cytoplasmic fragment to acquire motors. We have shown that soluble peptides derived from the cytoplasmic domain of APP when injected into the squid axon inhibit transport (Satpute-Krishnan et al, 2006; Bearer and Wu, 2019) through binding to kinesin (Seamster et al, 2012). Primary hippocampal cultures or slices from the mice used in this study could be implemented to tease apart the consequences of APP SwInd expression and plaque on transport of specific cargoes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence not only would the APP-containing vesicles lose transport capability, but other organelles would have to compete with the cytoplasmic fragment to acquire motors. We have shown that soluble peptides derived from the cytoplasmic domain of APP when injected into the squid axon inhibit transport (Satpute-Krishnan et al, 2006; Bearer and Wu, 2019) through binding to kinesin (Seamster et al, 2012). Primary hippocampal cultures or slices from the mice used in this study could be implemented to tease apart the consequences of APP SwInd expression and plaque on transport of specific cargoes.…”
Section: Discussionmentioning
confidence: 99%
“…This endocytosis step is at least partly mediated by Rab GTPases, such as RAB5A and RAB11, which enable the plasma membranes with viral glycoproteins entering the cell to form endocytic tubular membranes and provide viral capsids with an envelope, as seen in the case of HSV-1 [ 178 ]. Regarding anterograde and retrograde endosomal transport of viral particles in neurons, PC12 cells have been described to have viral capsids co-localizing with the trafficking regulator RAB5A, as well as the nerve growth factor NTRK1 (TrkA), which caused a higher expression of the amyloid precursor protein (APP) and altogether could account for the negative implications of some herpesviruses, such as HSV-1 in Alzheimer’s disease [ 179 ]. Interestingly, HSV-1 has been shown to induce the fragmentation of the Golgi network upon lytic infection in some cell types, such as Vero and HEp-2 cells [ 180 ].…”
Section: Lysosomal and Golgi-sorting Vesicles During Herpesvirus Ementioning
confidence: 99%
“…Bacteria and viruses also can induce AD, with both Porphyromonas gingivalis and Herpes simplex virus (HSV) having confirmed links with AD initiation and progression (Bearer and Wu, 2019;Dominy et al, 2019). Gingipains, produced by Porphyromonas gingivalis, is a toxic protease related to the phosphorylation of tau peptide and the ubiquitin pathology which can also increase the level of Aβ 42 in the brain (Bearer and Wu, 2019;Dominy et al, 2019). According to the results reported by Grenier et al,62.5 to 125 µg/ml of MYR had good inhibitory effect on Porphyromonas gingivalis, and this effect may be related to MYR's ability to chelate iron ions (Grenier et al, 2015).…”
Section: Myr and Dmy Play An Anti-ad Role By Inhibiting Bacteria And mentioning
confidence: 99%
“…Furthermore, physiological function disorders, such as oxidative stress, inflammation (Meraz-Ríos et al, 2013), abnormal autophagy and the damage of insulin signaling pathway (Zhang and Hölscher, 2020) were also found to cause serious damage to the brain and can lead to the manifestation of AD (Butterfield and Halliwell, 2019). Other factors are also reported as a driving force in the genesis and development of AD, such as the long-term infections of bacteria and viruses (Bearer and Wu, 2019;Dominy et al, 2019), and the dyshomeostasis of intestinal flora (Friedland, 2015).…”
Section: Introductionmentioning
confidence: 99%